Association Between Systemic Lupus Erythematosus and Cancer Morbidity and Mortality: Findings From Cohort Studies - Zhang, Min; Wang, Yizhou; Wang, Yutong; Bai, Ye; Gu, Dongqing (Frontiers in Oncology, 2022)
Background: Observational studies suggested that systemic lupus erythematosus (SLE) might be associated with increased cancer incidence and cancer-related death, however, the results are inconsistent. We aim to comprehensively estimate the causal relationships between SLE and cancer morbidity and mortality using a meta-analysis of cohort studies and Mendelian randomization. Methods: A systematic search was conducted using PubMed to identify cohort studies published before January 21, 2021. Meta-analysis was performed to calculate relative risk (RR) and corresponding 95% confidence intervals (CI). In addition, we further evaluated the potentially causal relationships identified by cohort studies using two-sample Mendelian randomization. Results: A total of 48 cohort studies involving 247,575 patients were included. We performed 31 main meta-analysis to assess the cancer risk and three meta-analyses to evaluate cancer mortality in SLE patients. Through meta-analyses, we observed an increased risk of overall cancer (RR=1.62, 95%CI, 1.47-1.79, P<0.001) and cancer-related death (RR=1.52, 95%CI, 1.36-1.70, P<0.001) in patients with SLE. Subgroup analysis by site-specific cancer showed that SLE was a risk factor for 17 site-specific cancers, including six digestive cancers (esophagus, colon, anus, hepatobiliary, liver, pancreatic), five hematologic cancers (lymphoma, Hodgkin’s lymphoma, non-Hodgkin lymphoma, leukemia, multiple myeloma), as well as cancer in lung, larynx, cervical, vagina/vulva, renal, bladder, skin, and thyroid. In addition, further mendelian randomization analysis verified a weakly association between genetically predisposed SLE and lymphoma risk (odds ratio=1.0004, P=0.0035). Conclusions: Findings from our study suggest an important role of SLE in carcinogenesis, especially for lymphoma.